BRAF Wild-type, PTEN Mutant Malignant Uveal Melanoma Arising Within a Mature Ovarian Teratoma: A Case Report and Review of the Literature. (July 2020) - Lengyel, Krisztina; Young, Fergus; Kucukmetin, Ali; Cresti, Nicola; Plummer, Ruth; Ralte, Angela; O'Donnell, Rachel Louise
Abstract : Mature cystic teratomas are common in women of all ages; however, malignant transformation within them is rare and difficult to diagnosis preoperatively. Primary melanoma of the ovary is exceptionally rare and only occurs in relation to a teratoma where it can originate from sporadic somatic mutagenesis within epidermal junctional melanocytes, through malignant transformation of a benign nevus formed within the mature cystic teratoma or from other well differentiated pigment-containing structures such as the uvea. We present a case of primary malignant melanoma arising within a mature cystic teratoma in a young patient, who ultimately developed widespread metastasis necessitating systemic therapy. Our case highlights the role of molecular medicine not only in forming an understanding the origin of the melanoma, but also guiding targeted systemic therapies. Alongside the case we present a review of the literature describing the incidence of molecular aberrations within melanoma as well as the established and emerging techniques and cytotoxic agents for malignant melanoma.